Aspectos biomecânicos das tarefas de levantar-se e sentar-se realizadas por indivíduos com osteoartrite dos joelhos leve e moderada - Petrella, Marina (Universidade Federal de São Carlos, 2019)
Sit-to-stand (STS) and stand-to-sit (STSit) tasks are daily performed and are among the complaints about physical function of individuals with knee osteoarthritis (KOA). Higher trunk flexion range of motion, lower magnitude of the affected knee joint moment and changes in the pattern of muscle activation have been observed in KOA and are pointed out as possible strategies to spare the affected knee. During the sit-to-stand and stand-to-sit tasks a higher trunk flexion can be used and be related with knee extensor and flexors cocontraction (Co). In addition, include volunteers only with bilateral KOA (OABI) or unilateral KOA (OAUNI) can be a challenge while studying the different degrees of KOA. The influence of these patterns of KOA involvement on the biomechanical and neuromuscular aspects of the tasks are unknown. Thus, the aim of this thesis was to compare biomechanical and neuromuscular parameters between the three groups (mild KOA, the moderate KOA and controls) in the STS and STSit. We also aim to compare the trunk and lower limb kinematics and kinetics in the sagittal plane and the magnitude of muscle activation during the STS transition between OAUNI and OABI. This thesis is divided into three Manuscripts. In the Manuscript-I, the STS was compared regarding trunk flexion, total support moment (TSM) and the hip, knee and ankle joint moments contribution for MTS across the groups. Considering the same group composition, Manuscript II presented the comparison of trunk flexion during STSit task and muscle activation magnitude and Co during both tasks. The relationship of these variables with greater trunk flexion also was investigated. In the third manuscript, the symmetry of the distribution of the vertical ground reaction force and the TSM were compared between individuals with OAUNI and OABI during the STSit. The TSM, muscle activation, Co, lower limb kinetics and kinematics and the knee extensor torque were also evaluated in the affected limb (or more affected for OABI) and were compared across the groups. In Manuscript-I it was observed that those with moderate KOA get up from chair with greater contribution of the hip joint moment to the magnitude of the MTS. This study also showed that in the early stages of the task those with mild and moderate KOA decreased the TSM without modifying the hip or ankle joint moments. Manuscript-II allowed identifying a higher trunk flexion strategy used by those with moderate KOA when compared both to mild KOA and controls. There was also a positive and significant association between trunk flexion and higher magnitude of Co during the stand-to-sit transition. Due to higher activation of gastrocnemius medialis during the STS transition and the lower rectus femoris activation while sitting, neuromuscular adaptations related to the moderate degree of KOA were suggested to be adopted. In study 3, individuals of OAUNI and OABI only differentiate one each other due to a lower MTS and higher trunk flexion in the extension phase of the STS task. The groups were considered similar and symmetrical regarding all the other variables.
Biomechanical aspects of the sit to stand and stand to sit tasks performed by individuals with mild and moderate knee osteoarthritis
Keywords: Osteoartrite; Cinemática; Dinâmica inversa; Eletromiografia; Quadríceps; Knee osteoarthritis; Kinetic; Inverse dynamics; Electromyography; Quadriceps; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL